2019
DOI: 10.1073/pnas.1907207116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of increasing vegetarian availability on meal selection and sales in cafeterias

Abstract: Shifting people in higher income countries toward more plant-based diets would protect the natural environment and improve population health. Research in other domains suggests altering the physical environments in which people make decisions (“nudging”) holds promise for achieving socially desirable behavior change. Here, we examine the impact of attempting to nudge meal selection by increasing the proportion of vegetarian meals offered in a year-long large-scale series of observational and experimental field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(128 citation statements)
references
References 42 publications
(50 reference statements)
8
102
0
1
Order By: Relevance
“…Future research can expand the findings of this study by including objective measures of behavior (e.g. see Garnett et al 2019), repeating the study in different cultural contexts, and exploring the moderating role of individuals' awareness of the link between meat consumption and global warming. While these results have mainly served a diagnostic purpose in understanding some of the socio-cognitive factors guiding intention and behaviors related to the reduction of meat consumption, they could be used to inform strategies for interventions that will encourage individuals to adapt a diet that is lower on meat intake in order to help mitigate the negative consequences of climate change.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Future research can expand the findings of this study by including objective measures of behavior (e.g. see Garnett et al 2019), repeating the study in different cultural contexts, and exploring the moderating role of individuals' awareness of the link between meat consumption and global warming. While these results have mainly served a diagnostic purpose in understanding some of the socio-cognitive factors guiding intention and behaviors related to the reduction of meat consumption, they could be used to inform strategies for interventions that will encourage individuals to adapt a diet that is lower on meat intake in order to help mitigate the negative consequences of climate change.…”
Section: Discussionmentioning
confidence: 97%
“…Previous TPB metaanalyses have underlined that the explanatory power of the model decreases when behavior is observed objectively rather than self-reported (Armitage and Conner 2001). Future (experimental) research could change behavior directly by manipulating the choice environment (Garnett et al 2019) or include both self-reported and more objective (e.g. observed) measures of reductions in meat consumption over time.…”
Section: Limitationsmentioning
confidence: 99%
“…We collected data on 23,103 unique customers, who ordered 110,266 entrées from April 3rd, 2017 to June 6th, 2018. As we were interested in food purchases for oneself, we identified and removed 21.3% of entrée orders (23,478), where customers purchased more than one entrée and were likely purchasing food for others.…”
Section: Participants and Assessment Periodmentioning
confidence: 99%
“…In another study, researchers sent daily text messages to undergraduate college students to reduce their red meat consumption, and found a self-reported reduction of roughly 1.5 portions of red meat over the course of a week, but did not assess objective measures or if other meat was substituted for red meat [22]. Another field experiment on college cafeteria choices found experimental evidence that an intervention that doubled the availability of vegetarian choices, from 25% to 50% of total offerings, increased vegetarian dish selection by 7.8 percentage points, from 19.1% to 26.9% [23]. While these interventions demonstrate effects that are similar or slightly larger in size than those we would anticipate from restaurant menu messaging, they require significantly greater operational costs, effort, and accommodation, such as repeated daily contact [22], calculating the carbon footprint of all dishes offered and updating this information as new dishes are introduced [21], or making extensive changes to offerings [23].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the popularity and availability of plant-based dishes is a strong modulator of societal acceptance and demand for those kinds of diets. For instance, increasing the offer from one to two plant-based meals in canteens, led to an increase of 40-80% of plant-based meal purchases, underlining the importance of availability as a strong driver 63 . Since the interest for plant-based diets has been changing dynamically in the last decade, researches should take period and location into account when comparing studies.…”
Section: Discussionmentioning
confidence: 99%